2014
DOI: 10.1007/s10384-014-0357-x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital blowout fracture location in Japanese and Chinese patients

Abstract: Orbital blowout fractures in Japanese and Chinese individuals occur most commonly in the medial wall. This is in contrast to previous reports on white individuals, who tend to sustain fractures involving the orbital floor rather than the medial wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…In contrast to other studies, the incidence of pure medial orbital blowout fractures has increased in Korea. [7][8][9] In March, 2015, there was one large-scale study about Chinese and Japanese blowout fracture type, 10 but there was still no large-scale study in Korean subjects as far as we know types in Korea.…”
mentioning
confidence: 99%
“…In contrast to other studies, the incidence of pure medial orbital blowout fractures has increased in Korea. [7][8][9] In March, 2015, there was one large-scale study about Chinese and Japanese blowout fracture type, 10 but there was still no large-scale study in Korean subjects as far as we know types in Korea.…”
mentioning
confidence: 99%
“…Previous studies have reported that the distribution of blowout fracture sites differed according to races 5,10 . In black patients, the medial wall is the most frequent blowout fracture site, whereas orbital floor fracture is more common in Caucasian and Asian patients 5 .…”
Section: Discussionmentioning
confidence: 96%
“…18 The orbital medial wall is prone to fracture due to this buckling force compared with the orbital floor because it is much thinner. 4,8,10 Additionally, as orbital contents decrease with age, older patients are at a greater risk of experiencing impact on the orbital rim instead of the globe. 11,19 In contrast, young patients are injured most frequently from focal trauma like assault or contusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbital floor involvement is common in orbital blowout fracture (around 50%) [ 2 , 3 ]. Diplopia and enophthalmos are the indication for surgical reconstruction of floor defect.…”
Section: Introductionmentioning
confidence: 99%